Gender Studies in Colombia. A Preliminary Discussion - Rodríguez Pizarro, Alba Nubia; Ibarra Melo, María Eugenia (Sociedad y Economía, 2013)
This paper presents the preliminary results of the state of art regarding the researchwith a gender and feminist perspective conducted in Colombia, by researchers from theUniversidad Nacional de Colombia Gender Studies School, the Universidad del Valle Gender,Woman, and Society Studies Center, and the Universidad de Antioquia InterdisciplinaryGender Studies Center, between 2000 and 2010. Three main aspects are analyzed:knowledge topics and problems, methodologies, and theoretical principles that revealdiverse and situated subjects in which gender, ethnicity, and class, as structuring categories,converge. As well, it is concluded that knowledge produced from this perspective isnot cleaved from action, which mirrors a fundamental characteristic of the gender andfeminist epistemologies.